2013
DOI: 10.1074/jbc.m113.499541
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfatase K, a Novel Lysosomal Sulfatase

Abstract: Background: Human sulfatases play key roles in physiology and cause numerous pathological conditions upon deficiency/misregulation. Results: ARSK is ubiquitously expressed, localizes to lysosomes, and shows arylsulfatase activity at acidic pH. Conclusion: ARSK is a novel lysosomal sulfatase acting on a ubiquitous substrate. Significance: ARSK functions in lysosomal degradation, possibly of glycosaminoglycans, and, in all probability, is associated with a non-classified lysosomal storage disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 38 publications
2
48
0
1
Order By: Relevance
“…Two of these sulfatases, arylsulfatase K and ARSG, have been described and characterized only recently after heterologous ectopic expression (2,3). In this study, detailed biochemical description of the endogenous ARSG enzyme is presented to understand in vivo expression, function, and properties of this enzyme, which is critical for the degradation of 3-O-sulfated glucosamine residues of heparan sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these sulfatases, arylsulfatase K and ARSG, have been described and characterized only recently after heterologous ectopic expression (2,3). In this study, detailed biochemical description of the endogenous ARSG enzyme is presented to understand in vivo expression, function, and properties of this enzyme, which is critical for the degradation of 3-O-sulfated glucosamine residues of heparan sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…3 By means of bioinformatics, 17 and 14 sulfatases have been identified in the human and murine genome, respectively, of which 13 have been characterized biochemically (1)(2)(3). Eight of these sulfatases are localized in lysosomes, where at least six of them are involved in the degradation of the GAGs heparan sulfate, dermatan sulfate, chondroitin sulfate, and keratan sulfate (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encoding arylsulfatase K (ARSK; EC 3.1.6.13) (ARSK in vertebrates; Arsk in rodents) was initially identified using bioinformatic methods through its conserved sulfatase active site signature sequence [1,6] and subsequently cloned, expressed in human cells, purified and biochemically characterized as an arylsulfatase [7], recently identified as catalysing the hydrolysis of the 2-O-sulfate group from 2-sulfoglucuronate [8]. Kinetic properties for human ARSK were similar to those of several other lysosomal sulfatases and an established role in the degradation of sulfated glycosaminoglycans has been identified [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low sequence identities with other human sulfatases have been reported, indicating that this gene and enzyme represents a distinct form of human sulfatase. Broad ARSK mRNA expression in human tissues has been reported which suggested that a ubiquitous biological arylsulfate substrate was the target for ARSK physiologically [7]. Previous studies have shown that it comprises several domains: an N-terminus signal peptide (residues ; five Ca 2+ binding sites (1 Ca 2+ per subunit); two active site residues (313Asp and 314His); and multiple N-glycosylation sites [7].…”
Section: Introductionmentioning
confidence: 99%